Conformation and Topology of Diacylglycerol Kinase in E.coli Membranes Revealed by Solid‐state NMR Spectroscopy1. (2nd April 2014) - Chen, Yanke; Zhang, Zhengfeng; Tang, Xinqi; Li, Jianping; Glaubitz, Clemens; Yang, Jun
Abstract Solid‐state NMR is a powerful tool for studying membrane proteins in a native‐like lipid environment. 3D magic angle spinning (MAS) NMR was employed to characterize the structure of E.coli diacylglycerol kinase (DAGK) reconstituted into its native E.coli lipid membranes. The secondary structure and topology of DAGK revealed by solid‐state NMR are different from those determined by solution‐state NMR and X‐ray crystallography. This study provides a good example for demonstrating the influence of membrane environments on the structure of membrane proteins.